2022
DOI: 10.3390/app12115560
|View full text |Cite
|
Sign up to set email alerts
|

Shifting of Meteorological to Hydrological Drought Risk at Regional Scale

Abstract: The drought along with climate variation has become a serious issue for human society and the ecosystem in the arid region like the Soan basin (the main source of water resources for the capital of Pakistan and the Pothohar arid region). The increasing concerns about drought in the study area have brought about the necessity of spatiotemporal analysis and assessment of the linkage between different drought types for an early warning system. Hence, the streamflow drought index (SDI) and standard precipitation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The trend analysis showed that in the case of the Dhoke Pathan basin, a declining trend of precipitation (Figure 4a), maximum temperature (Figure 4b), and minimum temperature (Figure 4c) increasing trend was observed during the years 1991-2015. Our results matched with Muhammad et al (2020) and Sarwar et al (2022), who performed analyses for precipitation, streamflow, maximum temperature, and minimum temperature for the Dhoke Pathan basin for the years 1983-2015. The overall results indicated that the declining trend of precipitation in the Soan River basin runoff also decreased due to the lack of precipitation, and hydrological drought occurred more rapidly (Hussain et al, 2021;Muhammad et al, 2020;Sarwar et al, 2022;Shahid et al, 2018;Waseem et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The trend analysis showed that in the case of the Dhoke Pathan basin, a declining trend of precipitation (Figure 4a), maximum temperature (Figure 4b), and minimum temperature (Figure 4c) increasing trend was observed during the years 1991-2015. Our results matched with Muhammad et al (2020) and Sarwar et al (2022), who performed analyses for precipitation, streamflow, maximum temperature, and minimum temperature for the Dhoke Pathan basin for the years 1983-2015. The overall results indicated that the declining trend of precipitation in the Soan River basin runoff also decreased due to the lack of precipitation, and hydrological drought occurred more rapidly (Hussain et al, 2021;Muhammad et al, 2020;Sarwar et al, 2022;Shahid et al, 2018;Waseem et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…In the Soan River basin, land use and land cover decrease the runoff due to the increase of barren land converted into agricultural land (Muhammad et al., 2020). In this study, the temporal results of hydrological drought increased in disturbed periods because streamflow decreased significantly in the Soan River basin due to the lack of precipitation, land use, land cover, and agriculture practices increased from 1999 to 2015 (Muhammad et al., 2020; Sarwar et al., 2022; Shahid et al., 2018).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations